MONITORING THE EFFECTIVENESS OF TREATMENT OF CICATRICIAL DEFORMITIES BASED ON THE CHANGES IN TNF-Α, MMP-9 AND VEGF LEVELS IN RAT SERUM - Hrechaniuk, David V.; Bambuliak, Andrii V.; Kuzniak, Nataliya B.; Bandrivsky, Yurii L.; Dmytrenko, Roman R.; Perebyinis, Pavlo P. (Eastern Ukrainian Medical Journal, 2026)
The aim of the study: to evaluate the efficacy of therapeutic strategies for scar deformities by determining the levels of TNF-α, MMP-9 and VEGF in the serum of rats during the dynamics of the experiment. Materials and methods. The experimental part of the study was carried out on 160 white Wistar rats. Four experimental groups were formed: control group – intact animals without surgically induced scar deformities; group I – animals that underwent correction of scar deformities using the gel «Nascar»; group II – animals that underwent correction of scar deformities using the combination of «Nascar»+CO2-laser; group III – animals that underwent correction of scar deformities using the complex technique of «Nascar»+CO2-laser+PRP microneedling. To evaluate the efficacy of the treatment, the levels of tumour necrosis factor-alpha (TNF-alpha), matrix metalloproteinase-9 (MMP-9) and vascular endothelial growth factor (VEGF) in rat serum were determined by enzyme-linked immunosorbent assay (ELISA). Blood was collected from the experimental rats by cutting the tip of the tail obliquely in a spiral into a leukocyte melanger with a razor blade. Results. As a result of the study, it was found that on day 60 of the experiment, the level of TNF-α in the serum of animals in group III («Nascar»+СО2-laser + PRP microneedling) corresponded to the reference values and was 1.7 times and 1.3 times lower than the same data in group I («Nascar») and group II («Nascar»+CO2-laser), respectively, p1<0.05, 0.01 and p2>0.05, 0.01, indicating a pronounced anti-inflammatory effect of PRP microneedling. The concentration of VEGF in the blood serum of rats in group III was within physiological limits and was 1.5 and 1.2 times lower than the same values in groups I and II («Nascar»+CO2-laser), respectively, p1<0.01, p2<0.05. A decrease in the activity of matrix metalloproteinases (MMP-9) was found to be 1.7 times and 1.4 times lower than monotherapy with «Nascar» gel (group I) and the combination of «Nascar»+CO2-laser (group II), respectively, p1, p2<0.01; Conclusions. Thus, the most effective therapeutic approach for correcting scar deformities was the integrated use of a hyaluronic acid-allantoin-onion extract gel, fractional CO2 laser therapy, and PRP microneedling. This multimodal strategy contributed to the attenuation of systemic inflammation, controlled angiogenesis, balanced neovascularization, and regulated extracellular matrix remodelling, ultimately minimizing the risk of pathological scar formation.